Nivel de violencia intrafamiliar percibida en tiempos de pandemia por estudiantes de los grados 6,7 y 8 de una Institución Educativa de Maicao-La Guajira. (2022)
Child abuse is one of the problems faced by children around the world, parents or caregivers use different forms of violence: physical, psychological or sexual, which violate the rights of children and cause serious damage to their development . The objective is to describe the level of domestic violence perceived by students in grades 6, 7 and 8 of an educational institution in Maicao La Guajira in the context of a pandemic.